První nálezy spontánní zaludecní kryptosporidiové infekce u krecíků (Phodopus roborovskii Satunin, 1903) - Pavlásek, I; Lávicka, M (Veterinarni medicina, 1995)
The desert hamster (Phodopus roborovskii Satunin, 1903) represents a new host of Cryptosporidium muris Tyzzer (1907), 1910. This very first finding was made in the laboratories of the National Veterinary Institute, Prague, Czech Republic. In September 1994 three 11-month and one 3-month desert hamsters were sent for laboratory examination. Parasitological examination post mortem of a 3-month desert hamster revealed "large" Cryptosporidium oocysts in excrements as well as in the contents of intestines. In all animals in which autopsy was carried out congestion of lungs, spleen and liver, acute catarrhal inflammation and flatulences in portions of gut were observed. Presence of morphologically identical oocysts of cryptosporidia was confirmed in the same group of desert hamsters also during parasitological reexamination carried out in October 1994. Applying the methods according to Breza (1957) and Pavlásek (1991) oocysts of the protozoon under study were detected in pooled samples of excrements of 3, 4, 5, 10 and 11-month animals. Two out of four live 2-3-month desert hamsters were infected naturally, both parents (10-11 months old), sent by the owner to our laboratory to be used for further observation. Both adult animals showed slight tremor, somnolence, rough hair and recumbent position, the male showed paresis of pelvic limbs. For four days in the laboratory conditions excrements of all six live desert hamsters, the interval being 2-12 hours, were examined and in four of them the finding of oocysts of the protozoon was repeatedly positive. Adult animals were euthanasied.(ABSTRACT TRUNCATED AT 250 WORDS)
Keywords: mužské pohlaví; nemoci hlodavců; Cricetinae; Rodent Diseases; zvířata; křečci praví; kryptosporidióza; Cryptosporidium; Cryptosporidiosis; Phodopus; Male; Animals